Results on Oscillation of Fractional Partial Differential Equation with Damping - Palanisamy, A.; Muthulakshmi, V. (Journal of Applied Nonlinear Dynamics, 2026)
In this manuscript, we primarily concentrate on the analysis of oscillatory behavior for the fractional order partial differential equation with damping term under Robin and Dirichlet boundary conditions. We obtained some new oscillation results by using the integral averaging technique and the generalized Riccati transformation. In the end, we have given two primary examples to illustrate the effectiveness of the obtained theory.